Value Flow Map: application and results in the disinfection center - Zeferino,Eliete Boaventura Bargas (2019)
ABSTRACT Objective: To identify and eliminate steps that do not add value for customers in the disinfection center. Method: We applied the Lean tool: Value Flow Map, using the concepts of gemba and kaizen in the work process of the disinfection unit for ventilatory care materials, aiming at improving such process. After performing a training with the team on the Lean concepts described above, applying the Value Flow Map in the gemba, analyzing the opportunities for improvement, and approving the changes, the Value Flow Map of the future state was devised and changes were implemented. Result: The time of the disinfection process was reduced in 2h37 and the financial resources required also decreased, in R$ 809.08/month. Conclusion: The application of Lean concepts presented positive results for the elimination of wastages in the disinfection center.